PATHOPHYSIOLOGY OF THE CARDIOVASCULAR SYSTEM IN GENERAL HYPOTHERMIA (SCIENTIFIC LITERATURE REVIEW) - Єхалов, Василь; Кравець, Ольга; Фесенко, Олександр (SWorldJournal, 2022)
In this review, the authors present data from the current scientific literature on the prevalence of general hypothermia, periodization of cold injury, main features of pathological changes in the human cardiovascular system in general hypothermia depend